PENGARUH LIKUIDITAS LEVERAGE OPERATING CAPACITY PROFITABILITAS TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN JASA SEKTOR PROPERTY DAN REAL ESTATE DI BEI 2019-2022 - Yuda Raviansah Silalahi; Wirda Lilia; Emma Novirsari (Journal Accounting International Mount Hope, 2024)
The objective of the research is to analyse the impact of liquidity, leverage, operating capacity, profitability against financial distress on real estate services companies listed on the Indonesian Stock Exchange. The research method used in this study is qualitative, this study uses purposive sampling techniques. samples of 80 companies in the Property and Real Estate department are presented in the BEI 2019 – 2022. The results of the research were that the liquidity variable affects the financial distress variable, the leverage variable does not affect the financial disaster variables, the operating capacity variables affects financial disasters, the profitability variables affect financial distresses, and then jointly the variables of liquidity, leverage, operating capability, and profitability affected the financial stress variables.